The Dynamics of Student-Centered Learning: Experiences from English Teachers in Situbondo Senior High Schools - Dhela Fika Nuzula Firdausi; Francisca Maria Ivone; Ekaning Dewanti Laksmi (Universitas Cokroaminoto Palopo, 2026)
This study aims to explore in depth the experiences of English teachers at Situbondo High School in implementing Student-Centered Learning (SCL). The focus covers three things: (1) the extent to which SCL principles are applied, (2) the benefits and challenges experienced by teachers during the implementation process, and (3) teacher strategies to maximize the benefits and overcome these challengesEmploying a sequential explanatory mixed-method design, quantitative data were collected from 33 English teachers through questionnaires, while qualitative data were gathered through classroom observations and semi-structured interviews with six teachers selected based on their implementation levels. The results indicate that the overall implementation of SCL was moderate to high level, reflecting teachers’ growing adaptation to student-centered practices. Among the seven principles, Teacher as Facilitator (M = 3.58) gained the highest scores, while Collaborative Learning (M = 2.99) and Balance of Power (M = 3.01) remained the lowest score but still in the high category. Some benefits were mentioned by teachers, including increased student motivation, confidence, involvement, and teamwork. However, a number of issues surfaced, such as time constraints, inadequate student preparation for independent learning, and a lack of media. To address these problems, teachers used a variety of strategies, including encouraging intrinsic motivation, providing students autonomy, integrating project-based and peer-tutoring activities, and utilizing technology to enhance instruction. This research contributes to the growing body of literature on SCL pedagogy in Asian EFL contexts and provides practical insights into effective strategies for optimizing SCL in secondary education.